The Challenges and Strategies of Nexus among Educational Research, Policy and Practice: Others’ Experiences - Mebratu, Belete Kebede (Bahir Dar Journal of Education, 2016)
This study examines the relationships among educational research, policy and practice from the historical and contemporary perspectives with the purpose of identifying strategies for better approaches to improving school practices. The research paper presents a brief history of educational research, challenges of rigor and quality of educational research, complexities of the relationships between researchers and practitioners, between policy makers and researchers, among research, policy and practice, and strategies to overcome the underlying constraints. Among the strategies are examinations into the options of the establishment of major research institutions that sort out what works best and provide standards of rigor for quality educational research; and the formulation of national education research policy that supports better forms of partnership and collaboration among policy makers, researchers and practitioners. To this end, the study explores some experiences from the U.S., Europe and others, and demonstrates how these experiences can be used as valuable lessons to advance a culture of partnership and collaboration among policy makers, researchers, and practitioners to improve education of the Ethiopian schools. The conclusions of the paper underline the need for the three parties to work as a team for the common goal of improving the quality of education that can contribute to the development of the country.